Improving treatment and liver fibrosis outcomes with metformin in HCV-HIV co-infected and HCV mono-infected patients with insulin resistance: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Doyle, Mary-Anne; Singer, Joel; Lee, Terry; Muir, Miriam; Cooper, Curtis
Abstract Background Approximately 180 million people worldwide, (3 % of the world's population) are infected with hepatitis C (HCV). Insulin resistance (IR) and type 2 diabetes (T2DM) are common extrahepatic manifestations of chronic HCV infection and associated with poor treatment and liver-related outcomes. The presence of these metabolic complications have been associated with poor response to interferon-based HCV antiviral therapy and increased risk of liver-related outcomes. Metformin, an insulin sensitizer is known to improve HCV treatment response and has been associated with a reduced risk of developing hepatocellular carcinoma (HCC). This study will evaluate the effect of metformin on preventing progression or promoting regression of liver fibrosis, rate of virologic cure (SVR) and other metabolic measures in HCV-HIV co-infected and HCV mono-infected study participants who have IR and are planning on initiating HCV treatment. Methods This study is a prospective 48-week single-centre, randomized, open-label, controlled trial of HIV-HCV co-infected and HCV mono-infected patients with IR (HOMA-IR ≥ 2.0) who are planning to initiate HCV antiviral therapy. Sixty participants will be recruited from The Ottawa Hospital Viral Hepatitis Clinic. Participants will be randomized in a 1:1 ratio to either arm 1, metformin 2 g (1 g twice daily) plus lifestyle, or to arm 2, lifestyle alone. The primary outcome will be the change in FibroScan® score (kPa) from baseline to week 12 (start of HCV treatment), the end of HCV treatment (week 24) and 24 weeks post HCV treatment (week 48). Secondary outcomes include changes in liver fibrosis using AST to platelet ratio index, changes in glucose and lipid levels, anthropometric measures, changes in alpha-fetoprotein levels, patient acceptability, and changes in dietary and physical activity parameters. Discussion This pilot study will be the first to evaluate the role of metformin on liver fibrosis in HCV-HIV co-infected and HCV mono-infected patients with IR receiving DAA HCV treatment. If metformin is effective in reducing liver fibrosis in this patient population, this will represent a well-tolerated, easy-to-administer, inexpensive therapy that will protect against negative HCV outcomes. This study will also be an opportunity to evaluate the impact of insulin resistance and hyperglycemia on viral clearance in HCV-infected patients treated with interferon-free regimens. Trial registration ClinicalTrials.govNCT02306070 version 4.0 (June 29, 2015)